PRIMARY ANALYSIS OF THE EXPRESSED SEQUENCE TAGS FROM A FULL-LENGTH ENRICHED cDNA LIBRARY OF SIBERIAN TIGER (PANTHERA TIGRIS ALTAICA) - Y. Guo; C.Q. Liu; L.S. Xu; T.F. Lu; D. Liu; X.C. Li; J.Z. Ma; Y.H. Ma; W.J. Guan (Journal of Animal and Plant Sciences, 2015)
Tiger is a special species only found in Asia and considered as one of the world’s most endangered species. In this study, a full-length enriched cDNA library was successfully constructed from Siberian tiger. The titers of primary and amplified libraries were 1.28×106 pfu/ml and 1.59×1010 pfu/ml respectively. The proportion of recombinants from unamplified library was 91.3% and average length of exogenous inserts was 1.06 kb. A total of 365 individual ESTs with sizes ranging from 264 to 1,378bps were then analyzed. Furthermore, 305 unigenes were successfully annotated and involved in 47 functions of the GO classification, Cell (278, 91.1%), Cellular process (302, 82.6%) and Binding (250, 82.0%) are the dominant terms. A total of 234 unigenes were assigned to 244 KEGG pathways, and the pathways with most representation are metabolic pathways (40, 17.1%). Among the 25 COG categories, general function prediction only cluster (52, 14.2%) represents the largest group, followed by translation, ribosomal structure and biogenesis (41, 11.2%), replication, recombination and repair (30, 8.2%), and only 9.9% ESTs (36) classified as novel genes. Moreover, this library provided a useful platform for the functional genome and transcriptome research for the P. tigris and other felid animals in future.
Keywords: Siberian tiger; Fibroblast cell; SMART cDNA library; Expressed sequence tags